2004
DOI: 10.1002/jso.20132
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life after colon interposition by necessity for esophageal cancer replacement

Abstract: Based on the SF-36 questionnaire, patients after colon interposition by necessity have a poor general quality of life. Even long after the operation they have a broad spectrum of persisting symptoms. Prior to surgery, patients should be informed about the disabling long-term functional outcome of a colon interposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 29 publications
(35 reference statements)
1
26
0
3
Order By: Relevance
“…The reasons for the increase in colonic reconstruction are that the prognosis of patients with gastric cancer has been improving and the incidence of secondary cancer of the esophagus has been increasing. Colonic interposition is a very useful technique that has gained wide acceptance in esophageal reconstruction for postgastrectomy patients [1][2][3][4][5][6]. The improvement in microsurgical techniques and availability of high-quality equipment has improved the safety of this technique [8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for the increase in colonic reconstruction are that the prognosis of patients with gastric cancer has been improving and the incidence of secondary cancer of the esophagus has been increasing. Colonic interposition is a very useful technique that has gained wide acceptance in esophageal reconstruction for postgastrectomy patients [1][2][3][4][5][6]. The improvement in microsurgical techniques and availability of high-quality equipment has improved the safety of this technique [8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that colonic interposition with preservation of not only the stomach but also the vagus is desirable as it enhances postoperative weight gain and results in fewer postoperative complications, including heartburn, dumping syndrome, etc. [1][2][3][4][5]. Some investigators have reported that even in cases in which preservation of the vagus nerve was not possible, reconstruction with the colon while preserving the stomach allowed higher caloric intake and better weight gain after surgery [6].…”
Section: Introductionmentioning
confidence: 99%
“…The most of them lose weight, but eventually stabilize at a new level that will not compromise your health, usually around 90% of preoperative weight 6,11,29 . Yasuda et al 30 .…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…Therefore from an experimental functional point of view, the isoperistaltic reconstruction should be considered more suitable. In the literature, as shown in Table 2, the peristaltic reconstruction is performed as a standard procedure at most institutions, 7,13,15,[17][18][19][20]25,26,[37][38][39][40][41] and only two reports by Isolauri et al 12 and Klink et al 30 used the antiperistaltic orientation more often than the peristaltic. Isolauri et al reported that there were no differences between isoperistaltic and antiperistaltic grafts observed in the radionuclide transit time, 42 while Neville and Najem described that eight adults with antiperistaltic segments complained for varying periods of diffi culty in swallowing and of acid regurgitation in the prone position.…”
Section: Use Of the Isoperistaltic Or Antiperistaltic Orientationmentioning
confidence: 99%